PELAKSANAAN PENGELOLAAN ZAKAT HARTA (MAL) SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 23 TAHUN 2011 DI KOTA YOGYAKARTA - Satrio Abdillah (JOURNAL EQUITABLE, 2022)
Zakat on wealth is Zakat that is given to people who are less able to help welfare and clean up the wealth of mankind. The purpose of this study is to find out the existence of a close relationship between government and zakat and to find out errors or weaknesses in Law Number 23 of 2011 that can harm parties who have noble goals. The research method used in this study is a normative juridical method. Data analysis was carried out in a qualitative descriptive manner, namely the data obtained were presented descriptively and analyzed qualitatively. The results of the study indicate that the management of zakat in the city of Yogyakarta is not effective, the mechanism mandated in the law alone does not work, but all elements and elements involved in the implementation of zakat management in the city of Yogyakarta are still running. It can be concluded that the articles that have the potential to harm the zakat amil in the city of Yogyakarta are not running well, even there are no or no cases of sanctions in the form of fines, confinement or other administrative sanctions to zakat amil for violations mandated in the legislation.